G protein estrogen receptor as a potential therapeutic target in Raynaud’s phenomenon - Fardoun, Manal; Mondello, Stefania; Kobeissy, Firas; Eid, Ali H. (Frontiers in Pharmacology, 2022)
Exaggerated cold-induced vasoconstriction can precipitate a pathogenesis called Raynaud’s phenomenon (RP). Interestingly, RP is significantly more prevalent in females than age-matched men, highlighting the potential implication of 17β-estradiol (E2) in the etio-pathogenesis of this disease. Indeed, we have previously reported that E2 stimulates the expression of vascular alpha 2C-adrenoceptors (α2C-AR), the sole mediator of cold-induced constriction of cutaneous arterioles. This induced expression occurs through the cyclic adenosine monophosphate → exchange protein activated by cAMP→ Ras-related protein 1→ c-Jun N-terminal kinase→ activator protein-1 (cAMP/Epac/Rap/JNK/AP-1 pathway). On the basis that estrogen-induced rapid cAMP accumulation and JNK activation occurs so rapidly we hypothesized that a non-classic, plasma membrane estrogen receptor was the mediator. We then showed that an impermeable form of E2, namely E2:BSA, mimics E2 effects suggesting a role for the membranous G-protein coupled estrogen receptor (GPER) in E2-induced α2C-AR expression. Our current working hypothesis and unpublished observations further cement this finding, as G1, a GPER agonist, mimics while G15, a GPER antagonist, abrogates estrogen’s effect on the expression of vascular α2C-AR. These, and other observations, highlight the potential of GPER as a tractable target in the management of RP, particularly in pre-menopausal women.